2005
DOI: 10.1176/appi.ps.56.7.810
|View full text |Cite
|
Sign up to set email alerts
|

An Actuarial Model of Violence Risk Assessment for Persons With Mental Disorders

Abstract: The multiple ICT model may be helpful to clinicians who are faced with making decisions about discharge planning for acutely hospitalized civil patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
184
0
8

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(195 citation statements)
references
References 10 publications
3
184
0
8
Order By: Relevance
“…This stereotype may persist, in part, because of researchers' focus on inpatients. Although fewer than 17% of persons with severe mental illness in the United States are hospitalized (59), nearly half of the studies that investigate violence in persons with severe mental illness examined only inpatients (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). Among these, the largest and most well-cited studies focused on involuntarily committed inpatients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This stereotype may persist, in part, because of researchers' focus on inpatients. Although fewer than 17% of persons with severe mental illness in the United States are hospitalized (59), nearly half of the studies that investigate violence in persons with severe mental illness examined only inpatients (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). Among these, the largest and most well-cited studies focused on involuntarily committed inpatients.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly 90% (27/31) of the studies of perpetration that we reviewed sampled patients from clinics or hospitals (11,12,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(46)(47)(48)(49)(50)(51); among studies that examined prevalence of victimization, all sampled persons in treatment. We need information on the estimated 5 million persons with severe mental illness in the United States who do not receive treatment (67).…”
Section: Investigate Community Populations Not Only Persons In Treatmentioning
confidence: 99%
“…Individuals with co-occurring disorders (CODs) are frequent utilizers of acute care facilities in the community, such as hospital emergency rooms or crisis units, and, lacking stabilization or long-term support, often cycle in and out of the correctional system (Peters, LeVasseur, & Chandler, 2004). Offenders with CODs are more likely to be arrested and to be incarcerated; to spend more time incarcerated (Bureau of Justice Statistics, 2006;Drake et al, 2001;Monahan et al, 2001Monahan et al, , 2005; and to return to prison following their release from custody, compared with offenders with a substance use disorder only (Lamberti, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Ryan et al, investigated violence prediction instruments derived from the MacArthur study [46][47][48][49] to evaluate their value in risk categorization. They found that the majority of patients categorized as high-risk were not later involved in any harmful behaviors [2].…”
Section: Limitation Of the Spjmentioning
confidence: 99%